2017
DOI: 10.3390/educsci7020063
|View full text |Cite
|
Sign up to set email alerts
|

The Flipped Classroom as a Pedagogical Tool for Leadership Development in Postgraduate Medical Education

Abstract: Abstract:Following a needs assessment among residents, a 10-module leadership curriculum was developed that included health care law and medical errors. An educational intervention using the flipped classroom model (FCM) was developed and we investigated (1) its effectiveness as a teaching method, and (2) the degree of knowledge acquisition of the content of the module. Thirty-four residents were selected using convenience sampling and were divided into an intervention group (n = 10) and a control group (n = 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…In a previous study we published, we described the phenomenon of “generational” expectations otherwise known as the “generational gap.” We explained how this phenomenon had impacted the educational landscape, and the demands it had placed on curricular design, which subsequently has resulted in attuning the choice of instructional methods to the needs of the “Millennial resident” (ie, collaborative, technologically adaptive, feedback-driven learners). 13 , 14 This has resulted in the emergence and adoption of educational strategies such as e-learning, the flipped classroom, and serious games (SGs) into medical education as novel teaching methods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study we published, we described the phenomenon of “generational” expectations otherwise known as the “generational gap.” We explained how this phenomenon had impacted the educational landscape, and the demands it had placed on curricular design, which subsequently has resulted in attuning the choice of instructional methods to the needs of the “Millennial resident” (ie, collaborative, technologically adaptive, feedback-driven learners). 13 , 14 This has resulted in the emergence and adoption of educational strategies such as e-learning, the flipped classroom, and serious games (SGs) into medical education as novel teaching methods.…”
Section: Introductionmentioning
confidence: 99%
“… 9 , 15 , 16 Furthermore, a SG is an educational context that we felt many residents would be familiar with and, like the flipped classroom, would appeal to the learning needs of residents. 14 , 17 Although we had reasons to assume that SGs would be a useful educational strategy, we lacked a clear understanding of whether it was an ideal intervention for teaching negotiation, a subset of our PM&L curriculum, and also how the MRs would perceive its utility and potential benefit for their learning. To define the appropriate research approach to investigate this phenomenon, we reconstructed the purpose of designing the leadership training module as well as the choice of the educational intervention using the typology of research purpose.…”
Section: Introductionmentioning
confidence: 99%
“…These include the flipped classroom, casebased discussion (CBD), peer teaching and the simulation clinic. In recent studies, we also demonstrated that the flipped classroom was a valuable method to teach certain aspects of leadership to residents (Lucardie et al 2017a;Lucardie et al 2017b). CBD has been proven to have potential in teaching analytical and decision-making skills, and we believe, liked the flipped classroom, that it would be equally beneficial to teach important aspects of management and leadership in residents (Jerrard 2005).…”
Section: Introductionmentioning
confidence: 76%
“…A Flipped classroom is a new pedagogical model in which students are provided with study resource material like teacher prepared notes, paper handouts, power points, videos as "pre-class assignment" to develop a basic understanding of the topic before class, and inclass, precious time is used for learner-centric activities such as presentation, clearing doubts, problem solving, group discussion and case discussion. 3 The teachers' roles is to monitor, guide, and support the learning process of their students. 4 The model was made popular by Eric Mazur emphasizing that the learning gains are approximately tripled with flipped class approach that focuses on the student and interactive learning.…”
Section: Introductionmentioning
confidence: 99%